2010
DOI: 10.1159/000272939
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cochlear Function on Auditory Temporal Resolution in Tinnitus Patients

Abstract: Our aim was to analyze the influence of subtle cochlear damage on temporal auditory resolution in tinnitus patients. Forty-eight subjects (hearing threshold ≤25 dB HL) were assigned to one of two experimental groups: 28 without auditory complaints (mean age, 28.8 years) and 20 with tinnitus (mean age, 33.5 years). We analyzed distortion product otoacoustic emission growth functions (by threshold, slope, and estimated amplitude), extended high-frequency thresholds, and the Gaps-in-Noise test. There were differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 73 publications
4
38
0
8
Order By: Relevance
“…The present results may be useful to in differentiating between middle and inner ear dysfunction, considering that DPOAE I/O functions slopes are affected only by inner ear conditions. However, in a study of tinnitus and DPOAE I/O functions at 4000 Hz, Sanches et al [19] found that normal-hearing individuals with tinnitus presented shallower slopes (slope measured from 20 to 60 dB peSPL) than the control group. They suggested that both the shallower slope and the reduced response at 80 dB in the DPOAE I/O functions might be associated with subclinical inner ear damages that were not detected in pure-tone audiometry.…”
Section: Discussionmentioning
confidence: 99%
“…The present results may be useful to in differentiating between middle and inner ear dysfunction, considering that DPOAE I/O functions slopes are affected only by inner ear conditions. However, in a study of tinnitus and DPOAE I/O functions at 4000 Hz, Sanches et al [19] found that normal-hearing individuals with tinnitus presented shallower slopes (slope measured from 20 to 60 dB peSPL) than the control group. They suggested that both the shallower slope and the reduced response at 80 dB in the DPOAE I/O functions might be associated with subclinical inner ear damages that were not detected in pure-tone audiometry.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Weisz20 suggests that even in individuals with normal hearing thresholds, the tinnitus may be related to the lack of afferent peripheral auditory information, agreeing with the view that the cochlear damage initiates a series of alterations in the central auditory system, resulting in tinnitus4, 7,17,21. It is expected that individuals with hearing loss have difficulty to obtain a good performance in tasks involving detection of silence gaps9,16,22,23. Sanches et al 24 showed the influence of hearing in frequencies above 8 kHz in the perception of silence gaps in the GIN test by individuals with tinnitus complaints. The present study reveals that the auditory deficit, even in individuals with normal pure tone thresholds (up to 25 dB HL), may already have had its onset as the Research Group presented higher hearing thresholds than the Control Group.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of the DPOAE after exposure to noise is described in the literature 14 , especially in the 5 and 6 kHz. Many studies show the possible use of the DPOAE I/O as an indirect measure of human cochlear nonlinearity 15,16 . The slope of the function can be evaluated and a threshold can be determined, as an additional procedure to check hearing function 6,11,17 .…”
Section: Introductionmentioning
confidence: 99%